2015
DOI: 10.1105/tpc.15.00163
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between Two bZIP Signaling Pathways Orchestrates Salt-Induced Metabolic Reprogramming in Arabidopsis Roots

Abstract: ORCID IDs: 0000-0003-3058-7570 (A.F.); 0000-0002-7910-9118 (J.S.); 0000-0001-8122-5460 (M.J.M.); 0000-0002-6332-1712 (J.V.-C.); 0000-0002-5605-7984 (J.H.)Soil salinity increasingly causes crop losses worldwide. Although roots are the primary targets of salt stress, the signaling networks that facilitate metabolic reprogramming to induce stress tolerance are less understood than those in leaves. Here, a combination of transcriptomic and metabolic approaches was performed in salt-treated Arabidopsis thaliana roo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
103
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(120 citation statements)
references
References 85 publications
3
103
0
1
Order By: Relevance
“…Further metabolic evidence for amino acid catabolism comes from Arabidopsis mutants defective in energy starvation signaling. In these lines, a similar suite of catabolic and gluconeogenic genes were regulated as observed here, including PPDK, and a subsequent altered metabolic profile was observed (Hartmann et al, 2015). However, it is difficult to discern metabolic fluxes from transcriptomic and metabolomic data except when start or end products of specific routes are quantified.…”
Section: Alternative Metabolic Reserve Mobilization As a Coordinated mentioning
confidence: 96%
“…Further metabolic evidence for amino acid catabolism comes from Arabidopsis mutants defective in energy starvation signaling. In these lines, a similar suite of catabolic and gluconeogenic genes were regulated as observed here, including PPDK, and a subsequent altered metabolic profile was observed (Hartmann et al, 2015). However, it is difficult to discern metabolic fluxes from transcriptomic and metabolomic data except when start or end products of specific routes are quantified.…”
Section: Alternative Metabolic Reserve Mobilization As a Coordinated mentioning
confidence: 96%
“…9), thus ruling out this possible link. Besides bZIP63, other bZIP genes such as bZIP1 and bZIP53 (Hartmann et al, 2015) could be involved in the regulation of anaerobic genes, a hypothesis requiring further work. The lower expression of DIN6, coding for an Asn synthase, observed in D-RAP2.12 and 35S: MA-RAP2.3 plants (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, it was commonly observed that the level of primary carbohydrates, Pro, and branched-chain amino acids (BCAAs) was strongly regulated by different combinations of bZIP TFs. For example, a bzip1 bzip53 double mutant was found to be affected in the coordination of BCAA catabolism under salt stress conditions, indicating a central function of these bZIPs in amino acid breakdown (Hartmann et al, 2015). Also, mutants defective in the bZIP63 TF showed increased levels of many proteinogenic amino acids, particularly under conditions of energy deprivation (Mair et al, 2015).…”
Section: Metabolic Signals Via Regulation Of Enzymes As Targets Of Snrk1mentioning
confidence: 99%
“…Particularly, the breakdown of BCAAs has recently gained more attention, leading to the conclusion that ETF/ETFQO is an essential pathway to donate electrons to the mETC and that amino acids are alternative substrates to maintain respiration under carbohydrate starvation (Cavalcanti et al, 2017). A functional link to SnRK1 via bZIP TFs has been suggested based on the observation that different bZIP TFs of the groups C and S were found to regulate amino acid breakdown, particularly Pro and BCAAs (Hanson et al, 2008;Dietrich et al, 2011;Hartmann et al, 2015). ETFQO can directly fuel electrons to the mETC and has recently been identified as direct target gene regulated by bZIP63 (Pedrotti et al, 2018), thereby providing the first functional link between SnRK1 and mitochondrial energy metabolism (Fig.…”
Section: Metabolic Signals Via Regulation Of Enzymes As Targets Of Snrk1mentioning
confidence: 99%
See 1 more Smart Citation